Transforming Maharah al-Kalam Learning in the Digital Era: A Theoretical Perspective on Modern Pedagogy - Mukhtar I. Miolo; Damhuri (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
The rapid development of digital technology has transformed foreign language learning, including Arabic speaking instruction (Maharah al-Kalam). This study aims to examine the digital transformation of Maharah al-Kalam learning through a theoretical review of modern pedagogical approaches. The study explores how digital technologies, multimedia platforms, mobile learning, and learner-centered pedagogies contribute to the development of Arabic speaking skills and communicative competence. This research employed a qualitative theoretical literature review design by analyzing scholarly publications related to Arabic language learning, digital pedagogy, Computer-Assisted Language Learning, Mobile-Assisted Language Learning, communicative language teaching, and technology-enhanced instruction. The data were collected through systematic literature searching and analyzed using qualitative content analysis and thematic analysis. The findings reveal that digital technologies significantly improve learner engagement, speaking practice opportunities, interaction, motivation, and learner autonomy. Tools such as animation applications, digital storytelling, social media platforms, artificial intelligence systems, and blended learning environments create more communicative and interactive Arabic speaking instruction. Modern pedagogical approaches, particularly communicative and constructivist models, further support the development of authentic speaking competence by promoting collaboration, active participation, and meaningful language use. However, several challenges remain, including limited technological infrastructure, insufficient teacher digital competence, vocabulary limitations, and unequal access to digital resources. The study concludes that the integration of digital technology and modern pedagogy offers transformative potential for Maharah al-Kalam learning when supported by appropriate instructional design, teacher preparedness, and communicative learning objectives.